Assess the efficacy of the combination of sports massage with heat therapy in improving range of motion in patients with shoulder pain? - Dewantara, Julian; Yuniana, Rina; Stefanska, Olga; Jurek, Joanna Michalina (Universitas Tanjungpura, 2024)
Background and Study Aim. This study aims to assess the efficacy of combining sports massage and heat therapy in enhancing joint range of motion among patients experiencing shoulder pain. Shoulder pain often coincides with restricted range of motion, impacting daily activities and overall quality of life. Sports massage is recognized for its ability to alleviate muscle tension and enhance blood circulation, while heat therapy is known to decrease muscle stiffness and enhance tissue elasticity. The integration of these two therapies is anticipated to offer synergistic advantages in addressing shoulder pain issues and improving joint flexibility.Material and Methods. The research design employed in this study is pre-experimental, utilizing a one-group pretest and posttest approach. The intervention involved administering a regular combination of sports massage and heat therapy to a group of patients with shoulder pain. Joint range of motion was assessed before and after the intervention using a pretest-posttest design. Statistical analyses, including t-tests and significance tests, were conducted to evaluate the difference between the mean pretest and posttest values.Results. The findings revealed a notable increase in the mean posttest measurements compared to the pretest values. Moreover, the significance test results indicated a significant effect (0.001 < 0.05), highlighting the effectiveness of combining sports massage and heat therapy in augmenting joint range of motion among patients with shoulder pain.Conclusion. These results strongly support the implementation of the combined therapy approach in shoulder pain rehabilitation to address limitations in joint range of motion. This study contributes to the scientific comprehension of the synergistic benefits associated with both therapies and lays the groundwork for refining treatment guidelines for individuals with similar conditions.